Pressure levels of patients followed by the Hiperdia Program - Gomes, Eduardo Tavares; Bezerra, Simone Maria Muniz da Silva (ABCS Health Sciences, 2018)
Introduction: The Hiperdia Program is an important action for the prevention of chronic non-communicable diseases in Brazil, particularly in the control of hypertension and diabetes. Objective: To compare the blood pressure of hypertensive patients from Hiperdia Program of the Family Health Strategy from Recife-PE, in relation to a sample of the local population not enrolled in a control program. Methods: Cross-sectional, analytical study with a quantitative approach, conducted with a group of 135 hypertensive patients from the Hiperdia program and 196 patients without obligatory link to a health service or without previous diagnosis of hypertension as a control group. Results: Patients enrolled in the Hiperdia program were controlled (73.3%) and mean diastolic and systolic blood pressure were lower than control group (p<0.001 and p=0.011, respectively). Conclusion: The results point to the importance of the program and the need for strategies to improve diagnosis in the general population.